Conscious experience a logical inquiry - Gupta, Anil 1949- (Harvard University Press, 2019)
This book aims to offer an account of conscious experience and of concepts that help us understand empirical reasoning and empirical dialectic. The account offered possesses, it is claimed, two virtues. First, it provides great theoretical freedom. It allows the theoretician freedom to radically reconceive the world. The theoretician may, for example, begin with the conception that colors are genuine qualities of physical bodies and may, in light of empirical findings, shift to the conception that colors are not genuine qualities at all. Second, the account grants empirical reason a great power to constrain: empirical reason can force a particular conception of the self and the world on the rational inquirer. These seemingly contrary virtues are reconciled through a novel treatment of presentation and appearances in the account offered of conscious experience and a novel treatment of ostensive definitions in the account offered of concepts. The argument of the book is buttressed by a critical study of the principal approaches to experience and reason found in the philosophical literature....